2015
DOI: 10.1039/c5ra01706h
|View full text |Cite
|
Sign up to set email alerts
|

NCN pincer palladium complexes based on 1,3-dipicolyl-3,4,5,6-tetrahydropyrimidin-2-ylidenes: synthesis, characterization and catalytic activities

Abstract: NCN pincer six-membered NHC palladium complexes were synthesized, characterized and used in Heck reaction of aryl bromides with olefines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Subsequently, two NCN pincer ring-expanded sixmembered NHCepalladium complexes containing 1,3dipicolyl-3,4,5,6-tetrahydropyrimidin-2-ylidenes have been synthesized by the direct metalation of the corresponding tetrahydropyridin-1-ium salts [79]. Catalytic activity study showed that the complexes catalyzed the Heck reaction of aryl bromides with acrylate/styrene efficiently using Et 3 N as base and DMA as a solvent.…”
Section: Mizorokieheck Reactionmentioning
confidence: 99%
“…Subsequently, two NCN pincer ring-expanded sixmembered NHCepalladium complexes containing 1,3dipicolyl-3,4,5,6-tetrahydropyrimidin-2-ylidenes have been synthesized by the direct metalation of the corresponding tetrahydropyridin-1-ium salts [79]. Catalytic activity study showed that the complexes catalyzed the Heck reaction of aryl bromides with acrylate/styrene efficiently using Et 3 N as base and DMA as a solvent.…”
Section: Mizorokieheck Reactionmentioning
confidence: 99%
“…112 NHC-PdCl 2 (pyridine) complexes (C78a-f ) for the coupling of various aryl chlorides under mild condi-tions in aqueous DMF with low catalyst loadings (0.01 mol%) resulted in high yields (Table 8, entries 44-47). 113 The complexes C79 were applied in the reaction of phenylboronic acid with aryl halides in neat water, the complexes 79b and 79d displayed the highest catalytic activity at 100 • C (Table 8, entries [48][49][50][51], and the catalytic system could be reused several times with only a slight decrease in its activity. Water-soluble Pd(II)-NHC complex, C80, where NHC is a dianionic sulfonated and sterically hindered catalyst, was used for the Suzuki coupling of aryl chlorides and boronic acids in mixtures i PrOH/water or water (Table 8, entries 52-55).…”
Section: Biphasic Catalysismentioning
confidence: 99%
“…• C (Table 8, entries [48][49][50][51], and the catalytic system could be reused several times with only a slight decrease in its activity. 114 Water-soluble Pd(II)-NHC complex, C80, where NHC is a dianionic sulfonated and sterically hindered catalyst, was used for the Suzuki coupling of aryl chlorides and boronic acids in mixtures i PrOH/water or water (Table 8, entries 52-55).…”
mentioning
confidence: 99%
“…Complexes B on the other hand were the product of targeted, modular synthesis (M = Cr, Fe). , Iron derivatives in particular were extensively investigated, and the strongly electron-donating ligand proved to be capable to stabilize complexes having the metal in formal oxidation states 0, I, II, and III. , Some of these iron complexes were shown to be proficient at promoting lactide polymerization . The photophysical properties of derivatives C (M = Ru, Pd, Pt) have been discussed, while palladium derivatives D have shown catalytic activity toward Heck coupling . Pincer complexes E , (M = Ni, Rh, Ir) incorporating a polycyclic, chiral backbone derived from (1 R )-camphor have been investigated as catalysts for hydrogenation and transfer hydrogenation reactions .…”
Section: Introductionmentioning
confidence: 99%
“…9c The photophysical properties of derivatives C (M = Ru, Pd, Pt) have been discussed, 10 while palladium derivatives D have shown catalytic activity toward Heck coupling. 11 Pincer complexes E, (M = Ni, Rh, Ir) incorporating a polycyclic, chiral backbone derived from (1R)-camphor have been investigated as catalysts for hydrogenation and transfer hydrogenation reactions. 12 Only two types of PCP pincer ligands incorporating six-membered NHCs in the central positions have been reported to date.…”
Section: ■ Introductionmentioning
confidence: 99%